2016
DOI: 10.1007/s11252-016-0581-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biodiversity and environment-related attitude on perception of urban green space

Abstract: Green space in cities contributes to the quality of life for city dwellers, e.g., by increasing the opportunity for recreation. However, perception of urban green space is influenced by multiple factors. We investigated effects of biodiversity and environment-related attitudes on visual and auditory perceptions of urban green space. Field measurements of biodiversity were conducted in six sites across an urban gradient in Gothenburg, Sweden, and three categories of biodiversity-high, medium, low-were establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 50 publications
7
68
1
4
Order By: Relevance
“…Similarly, people that associate tranquility to social sounds could be expected to notice human voices more often. Recently, it was observed that environment-related attitudes influence perceptions of green space, in particular that nature-oriented attitude leads to valuing natural sounds more highly [19]. This result could support our first hypothesis, yet the questions about natural sounds used in this study were more oriented towards valuation than towards observation.…”
Section: Introductionsupporting
confidence: 84%
“…Similarly, people that associate tranquility to social sounds could be expected to notice human voices more often. Recently, it was observed that environment-related attitudes influence perceptions of green space, in particular that nature-oriented attitude leads to valuing natural sounds more highly [19]. This result could support our first hypothesis, yet the questions about natural sounds used in this study were more oriented towards valuation than towards observation.…”
Section: Introductionsupporting
confidence: 84%
“…urban woodlands) were linked to more positive nature-sound-related evaluations and higher importance for experiencing bird songs than in areas with perceived low naturalness (parks, allotments and lawns). It should be noted, however, that this difference partly could be influenced by the environment-related attitudes of people living nearby our study areas [30]. Independently of the type of naturalness in the urban green areas, women evaluated natural sounds and bird song higher than men did.…”
Section: Discussionmentioning
confidence: 87%
“…The measure comprised five statements, with a Cronbach's α of 0.81; indicating high reliability: ‘Sounds of nature give me a stronger perception of the site’; ‘Rustling trees make me feel calm’; ‘Bird song in the area makes me feel calm’; ‘Human voices make me feel calm’; and ‘Noise from the city and traffic interferes with my perception of the area’ (see also [24] and [30]).…”
Section: Methodsmentioning
confidence: 99%
“…As has been suggested elsewhere there is often a mismatch between people's perception of, and actual, species richness (Dallimer et al, 2012;Hassall, 2014) (Figure 1), but there is increasing evidence that in some settings, peoples subjective perceptions of species diversity may reflect objective measures (Gunnarsson, Knez, Hedblom, & Sang, 2017). So, while people may not explicitly recognize biological diversity, there are aspects of it that may be appreciated in terms of well-being gains.…”
Section: What Is Biological (Bio)diversitymentioning
confidence: 96%